A Middle and Late Devensian sequence from the northern part of Kents Cavern (Devon, UK) - Rob Dinnis; John Boulton; Barry Chandler; Jesse Davies; Jennifer C. French; Thomas Higham; Louisa Jáuregui; Mark Lewis; Matthias Meyer; Danielle Schreve; Chris Stringer; Chris Proctor (Journal of Quaternary Science, 2025)
1920s/30s excavation of a Middle Devensian sequence in the northern part of Kents Cavern recovered important Late Middle and Early Upper Palaeolithic archaeological material, including Britain's oldest known Homo sapiens remains. Questions remain about this material, including how it came to be in the cave. Judged by the recorded distribution of finds it may have entered via the Northeast Gallery. A previously unrecorded entrance into the cave from the Northeast Gallery was identified in 2014, and a column through the entrance's sedimentary fill was excavated during 2015–2016. The results of that work are reported here. The entrance retains an intact and well‐stratified Pleistocene sequence comparable to the ‘Cave Earth’ unit described previously inside the cave. The uppermost part of the newly recognised Northeast Gallery entrance sequence has been removed by historical excavation, with most of the remaining sediments spanning the Middle Devensian and earlier part of the Late Devensian. The sequence contains bone and pollen, and ancient mammalian DNA is preserved within the sediments. The base of the Northeast Gallery entrance sequence is formed of a clayey diamict comparable to the cave's ‘Breccia’ unit, a deposit currently understood as Middle Pleistocene, and previously identified only in Kents Cavern's southern chambers. Comparison of the excavated sequence with the historical record of the Vestibule excavation shows that the basal cave earth deposits in the Northeast Gallery entrance are significantly higher than those inside the cave. Although requiring further work to confirm, this suggests that the Northeast Gallery could have played a major role in the accumulation of material in the Vestibule during the Middle Devensian.

The applicability of regional red list assessments for soil invertebrates: first assessment of five native earthworm species in Canada - Helen R. P. Phillips; George G. Brown; Sam W. James; Jérôme Mathieu; John Warren Reynolds; Maheshi E. Dharmasiri; Claire L. Singer; Maria J. I. Briones; Heather C. Proctor; Erin K. Cameron (Biodiversity and Conservation, 2025)
Earthworms (Annelida: Clitellata: Crassiclitellata) are prominent members of the soil community, important to many ecosystem functions. Despite this, and like many other soil invertebrates, they are rarely considered in conservation assessments, including the International Union for Conservation of Nature (IUCN) Red List assessments used to assess species’ extinction risk. To investigate the applicability of the IUCN Regional Red Listing protocol to soil invertebrates, we assessed the conservation status of five earthworm species native to Canada using this protocol and all available occurrence records. In Canada, no earthworm species have yet been assessed by the Committee on the Status of Endangered Wildlife in Canada (COSEWIC). Due to the lack of data on population sizes and their trends, all five species were assessed using their Extent of Occurrence (EOO) (Criterion B). One species was assessed as Vulnerable ( Arctiostrotus vancouverensis) , two were assessed in non-threatened categories ( A. perrieri and Sparganophilus tamesis ), and two were assessed as Data Deficient ( A. fontinalis and Toutellus oregonensis ). For the majority, the main threats identified were the continuing loss of potential habitat due to land conversion and resource exploitation, as well as the effects of climate change. Increasing the amount of data, including but not limited to distribution and habitat preferences, would make the assessment process easier and status decisions better supported. By undertaking regional assessments for five native earthworm species in Canada, we show that Regional Red List assessments are feasible for soil invertebrates.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Corridor‐based approach with spatial cross‐validation reveals scale‐dependent effects of geographic distance, human footprint and canopy cover on grizzly bear genetic connectivity - Eric C. Palm; Erin L. Landguth; Zachary A. Holden; Casey C. Day; Clayton T. Lamb; Paul F. Frame; Andrea T. Morehouse; Garth Mowat; Michael F. Proctor; Michael A. Sawaya; Gordon Stenhouse; Jesse Whittington; et al. (Molecular Ecology, 2023)
Understanding how human infrastructure and other landscape attributes affect genetic differentiation in animals is an important step for identifying and maintaining dispersal corridors for these species. We built upon recent advances in the field of landscape genetics by using an individual‐based and multiscale approach to predict landscape‐level genetic connectivity for grizzly bears ( Ursus arctos ) across ~100,000 km 2 in Canada's southern Rocky Mountains. We used a genetic dataset with 1156 unique individuals genotyped at nine microsatellite loci to identify landscape characteristics that influence grizzly bear gene flow at multiple spatial scales and map predicted genetic connectivity through a matrix of rugged terrain, large protected areas, highways and a growing human footprint. Our corridor‐based modelling approach used a machine learning algorithm that objectively parameterized landscape resistance, incorporated spatial cross validation and variable selection and explicitly accounted for isolation by distance. This approach avoided overfitting, discarded variables that did not improve model performance across withheld test datasets and spatial predictive capacity compared to random cross‐validation. We found that across all spatial scales, geographic distance explained more variation in genetic differentiation in grizzly bears than landscape variables. Human footprint inhibited connectivity across all spatial scales, while open canopies inhibited connectivity at the broadest spatial scale. Our results highlight the negative effect of human footprint on genetic connectivity, provide strong evidence for using spatial cross‐validation in landscape genetics analyses and show that multiscale analyses provide additional information on how landscape variables affect genetic differentiation.

Cryptic carnivores: Intercontinental sampling reveals extensive novel diversity in a genus of freshwater annelids - Joseph M. Mack; Mårten Klinth; Svante Martinsson; Robert Lu; Hannah Stormer; Patrick Hanington; Heather C. Proctor; Christer Erséus; Alexandra E. Bely (Molecular Phylogenetics and Evolution, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

DNA barcodes expose unexpected diversity in Canadian mites - Monica R. Young; Heather C. Proctor; Jeremy R. deWaard; Paul D. N. Hebert (Molecular Ecology, 2019)
Mites (Arachnida: Acariformes, Parasitiformes) are the most abundant and species‐rich group of arthropods in soil, but are also diverse in freshwater habitats, on plants, and as symbionts of larger animals. However, assessment of their diversity has been impeded by their small size and often cryptic morphology. As a consequence, published estimates of their species richness span more than two orders of magnitude (0.4–114 million). In this study we employ DNA barcoding and the Barcode Index Number (BIN) system to investigate mite diversity at over 1,800 sites across Canada, primarily from soil and litter habitats with smaller contributions from freshwater, plants, and animal hosts. Barcodes from 73,394 specimens revealed 7,077 BINs with representatives from all four orders (Ixodida, Mesostigmata, Sarcoptiformes, Trombidiformes) and 60% (186) of the known families. The BIN total is 2.4 times the number of species previously recorded from Canada (2,999), reflecting the unexpectedly high richness of several families. Richness projections suggest that more than 28,000 BINs occur at the sampled locations, indicating that the Canadian mite fauna almost certainly includes more than 30,000 species—a total similar to that for the most diverse insect order in Canada, Diptera. This unexpected diversity was partitioned into highly dissimilar, spatially‐structured assemblages that likely reflect dispersal limitation and environmental heterogeneity. Further sampling of a greater diversity of habitats will refine understanding of mite diversity in Canada, but similar analyses in other geographic regions will be essential to ascertain their diversity at a global scale.

The burning issue of dung in archaeobotanical samples: a case-study integrating macro-botanical remains, dung spherulites, and phytoliths to assess sample origin and fuel use at Tell Zeidan, Syria - Alexia Smith; Lucas Proctor; Thomas C. Hart; Gil J. Stein (Vegetation History and Archaeobotany, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Feather mites play a role in cleaning host feathers: New insights from DNA metabarcoding and microscopy - Jorge Doña; Heather Proctor; David Serrano; Kevin P. Johnson; Arnika Oddy‐van Oploo; Jose C. Huguet‐Tapia; Marina S. Ascunce; Roger Jovani (Molecular Ecology, 2019)
Parasites and other symbionts are crucial components of ecosystems, regulating host populations and supporting food webs. However, most symbiont systems, especially those involving commensals and mutualists, are relatively poorly understood. In this study, we have investigated the nature of the symbiotic relationship between birds and their most abundant and diverse ectosymbionts: the vane‐dwelling feather mites. For this purpose, we studied the diet of feather mites using two complementary methods. First, we used light microscopy to examine the gut contents of 1,300 individual feather mites representing 100 mite genera (18 families) from 190 bird species belonging to 72 families and 19 orders. Second, we used high‐throughput sequencing ( HTS ) and DNA metabarcoding to determine gut contents from 1,833 individual mites of 18 species inhabiting 18 bird species. Results showed fungi and potentially bacteria as the main food resources for feather mites (apart from potential bird uropygial gland oil). Diatoms and plant matter appeared as rare food resources for feather mites. Importantly, we did not find any evidence of feather mites feeding upon bird resources (e.g., blood, skin) other than potentially uropygial gland oil. In addition, we found a high prevalence of both keratinophilic and pathogenic fungal taxa in the feather mite species examined. Altogether, our results shed light on the long‐standing question of the nature of the relationship between birds and their vane‐dwelling feather mites, supporting previous evidence for a commensalistic–mutualistic role of feather mites, which are revealed as likely fungivore–microbivore–detritivore symbionts of bird feathers.

Differential Morphological and Biochemical Recovery from Chemotherapy-Induced Peripheral Neuropathy Following Paclitaxel, Ixabepilone, or Eribulin Treatment in Mouse Sciatic Nerves - B. M. Cook; K. M. Wozniak; D. A. Proctor; R. B. Bromberg; Y. Wu; B. S. Slusher; B. A. Littlefield; M. A. Jordan; L. Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2018)

Cardiovascular Effects of the MEK Inhibitor, Trametinib: A Case Report, Literature Review, and Consideration of Mechanism - Mary Banks; Karen Crowell; Amber Proctor; Brian C. Jensen (Cardiovascular Toxicology, 2017)

Diet, gut microbiota and cognition - Cicely Proctor; Parameth Thiennimitr; Nipon Chattipakorn; Siriporn C Chattipakorn (Metabolic Brain Disease, 2017)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Can freshwater mites act as forensic tools? - Heather C. Proctor (Experimental and Applied Acarology, 2009)

Revisiting the meiofauna paradox: dispersal and colonization of nematodes and other meiofaunal organisms in low- and high-energy environments - Matthew J. Boeckner; Jyotsna Sharma; H. C. Proctor (Hydrobiologia, 2009)

Sea lice, Lepeophtheirus salmonis , transfer between wild sympatric adult and juvenile salmon on the north coast of British Columbia, Canada - A S Gottesfeld; B Proctor; L D Rolston; C Carr‐Harris (Journal of Fish Diseases, 2009)
We examine sea lice, Lepeophtheirus salmonis , on juvenile and adult salmon from the north coast of British Columbia between 2004 and 2006 in an area that does not at present contain salmon farms. There is a pronounced zonation in the abundance of L. salmonis on juvenile pink salmon, Oncorhynchus gorbuscha , in the Skeena and Nass estuaries. Abundances in the proximal and distal zones of these estuaries are 0.01 and 0.05 respectively. The outer zones serve as feeding and staging areas for the pink salmon smolts. Returning Chinook, Oncorhynchus tshawytscha , and coho salmon, Oncorhynchus kisutch , concentrate in these areas. We collected data in 2006 to examine whether L. salmonis on returning adult salmon are an important source of the sea lice that appear on juvenile pink salmon. Nearly all (99%) of the sea lice on returning Chinook and over 80% on coho salmon were L. salmonis. Most of the L. salmonis were motile stages including many ovigerous females. There was a sharp increase in the abundance of sea lice on juvenile pink salmon smolts between May and July 2006 near the sites of adult captures. As there are no salmon farms on the north coast, few sticklebacks, Gasterosteus aculeatus , and very few resident salmonids until later in the summer, it seems that the most important reservoir of L. salmonis under natural conditions is returning adult salmon. This natural source of sea lice results in levels of abundance that are one or two orders of magnitude lower than those observed on juvenile pink salmon in areas with salmon farms such as the Broughton Archipelago.

Integration of Mouse Phenome Data Resources - John M. Hancock; Niels C. Adams; Vassilis Aidinis; Andrew Blake; Judith A. Blake; Molly Bogue; Steve D. M. Brown; Elissa J. Chesler; Duncan Davidson; Christopher Duran; Janan T. Eppig; Valérie Gailus-Durner; et al. (Mammalian Genome, 2008)

Soil acidity and nutrient deficiency in central Amazonian heath forest soils - Flávio J. Luizão; Regina C. C. Luizão; John Proctor (Plant Ecology, 2007)

Fine root growth and nutrient release in decomposing leaf litter in three contrasting vegetation types in central Amazonia - Regina C. C. Luizão; Flávio J. Luizão; John Proctor (Plant Ecology, 2007)

Responses of ground-active beetle assemblages to different styles of reforestation on cleared rainforest land - Peter S. Grimbacher; Carla P. Catterall; John Kanowski; Heather C. Proctor (Biodiversity and Conservation, 2007)

Mesostigmatid Mites (Acari: Mesostigmata) on Rainforest Tree Trunks: Arboreal Specialists, but Substrate Generalists? - Frédéric Beaulieu; David E. Walter; Heather C. Proctor; Roger L. Kitching; Florian Menzel (Experimental and Applied Acarology, 2006)

Microclimate, light adaptation and desiccation tolerance of epiphytic bryophytes in two Venezuelan cloud forests - Yelitza León‐Vargas; Stefan Engwald; Michael C. F. Proctor (Journal of Biogeography, 2006)
Aim Analysis of microclimate factors and physiological responses determining survival and growth of epiphytic bryophytes in the lower canopy and trunk space of north‐Andean cloud forests. Location Two cloud forests at 2000–2400 m in the northern Andes near Mérida, Venezuela. Methods Data‐logging of dry and wet‐season temperature, relative humidity (r.h.) and photosynthetically‐active radiation (PAR) for month‐long periods, and laboratory measurements of desiccation tolerance and light responses of selected epiphytic bryophytes. Results Rainfall averages 20 mm or less in January and February, and 200 mm or more from August to October, but is very variable at all seasons. The proportion of time ‘wet’ (continuous 100% r.h.) in the months sampled ranged from 8.5% to 52.2% or more; a dry/wet‐season range between 20% and 40% is probably commoner. The length of ‘wet’ and ‘dry’ periods approximated log‐normal distributions, with mid‐points for wet periods ranging from 2.8 to 10.7 h, and dry periods from 6.2 to 17.1 h. The longest recorded dry period was 143 h. Humidity typically rose during the night to > 90% r.h., reaching 100% for significant periods (implying cloudwater (fog) deposition) on about one night in two in all seasons. Of six bryophytes of pendulous growth form, all survived periods of at least a few days’ desiccation; most recovered better from high than low humidities. Measured 95% light‐saturation values ranged from 110 to 256 μ mol m −2 s −1 , somewhat but not greatly higher than ambient light levels Main conclusions Environmental conditions in the cloud forests are probably near‐optimal for epiphytic bryophytes, but in even the wettest forest these plants must tolerate at least short periods of drying at any time of year, and longer periods seasonally. Interception of cloudwater droplets from moving air is likely to be an important source of water for bryophytes of pendant and other diffuse life forms, especially in periods of low rainfall. Absorption of water from near‐saturated air is probably of little physiological significance. Bryophytes of these life‐forms are notably conspicuous in tropical‐montane cloud forests. They remain prominent into humid temperate regions such as southern Chile, New Zealand and Macaronesia, but progressively disappear at higher latitudes with the stresses of increasing seasonality.

Red, distasteful water mites: did fish make them that way? - Heather C. Proctor; Neera Garga (Experimental and Applied Acarology, 2002)

A three thousand year record of North Atlantic climate - Proctor C.; Baker A.; Barnes W. (Climate Dynamics, 2002)

Extracting aquatic mites from stream substrates: a comparison of three methods - Heather C. Proctor (Experimental and Applied Acarology, 2001)

A thousand year speleothem proxy record of North Atlantic climate from Scotland - C. J. Proctor; A. Baker; W. L. Barnes; M. A. Gilmour (Climate Dynamics, 2000)

Synergistic Effect of Formulated Plasmid and Needle-Free Injection for Genetic Vaccines - Khursheed Anwer; Keith A. Earle; Mei Shi; Jijun Wang; Russell J. Mumper; Belinda Proctor; Kimberly Jansa; Harry C. Ledebur; Stephen Davis; William Eaglstein; Alain P. Rolland (Pharmaceutical Research, 1999)

Effects of specimen handling and otolith preparation on concentration of elements in fish otoliths - C. H. Proctor; R. E. Thresher (Marine Biology, 1998)

Feeding behaviour and phylogeny: observations on early derivative Acari - David Evans Walter; Heather C. Proctor (Experimental and Applied Acarology, 1998)